Planning and Management – the Most Neglected Activities in Lexicography - van Schalkwyk, D.J. (Lexikos, 1999)
Lexicography has a long history of ineffective planning and inefficient management. This article applies the methods of general planning and management to the planning and management of a lexicographic unit.Keywords: planning; management; mission statement; strategic focus areas; performance areas; situational description; internal environment; external environment; environmental analysis; restricting factors; supporting factors; environmental tendencies; scenario; future strategic position; goals; action plan; production management; management system